Bilateral and symmetric glycinergic and glutamatergic projections from the LSO to the IC in the CBA/CaH mouse - Williams, Isabella R.; Ryugo, David K. (Frontiers in Neural Circuits, 2024)
Abstract Auditory space has been conceptualized as a matrix of systematically arranged combinations of binaural disparity cues that arise in the superior olivary complex (SOC). The computational code for interaural time and intensity differences utilizes excitatory and inhibitory projections that converge in the inferior colliculus (IC). The challenge is to determine the neural circuits underlying this convergence and to model how the binaural cues encode location. It has been shown that midbrain neurons are largely excited by sound from the contralateral ear and inhibited by sound leading at the ipsilateral ear. In this context, ascending projections from the lateral superior olive (LSO) to the IC have been reported to be ipsilaterally glycinergic and contralaterally glutamatergic. This study used CBA/CaH mice (3-6 months old) and applied unilateral retrograde tracing techniques into the IC in conjunction with immunocytochemical methods with glycine and glutamate transporters (GlyT2 and vGLUT2, respectively) to analyze the projection patterns from the LSO to the IC. Glycinergic and glutamatergic neurons were spatially intermixed within the LSO, and both types projected to the IC. For GlyT2 and vGLUT2 neurons, the average percentage of ipsilaterally and contralaterally projecting cells was similar (ANOVA, p = 0.48). A roughly equal number of GlyT2 and vGLUT2 neurons did not project to the IC. The somatic size and shape of these neurons match the descriptions of LSO principal cells. A minor but distinct population of small (<40 µm2) neurons that labeled for GlyT2 did not project to the IC; these cells emerge as candidates for inhibitory local circuit neurons. Our findings indicate a symmetric and bilateral projection of glycine and glutamate neurons from the LSO to the IC. The differences between our results and those from previous studies suggest that species and habitat differences have a significant role in mechanisms of binaural processing and highlight the importance of research methods and comparative neuroscience. These data will be important for modeling how excitatory and inhibitory systems converge to create auditory space in the mouse.